2020
DOI: 10.3390/ijerph17082739
|View full text |Cite
|
Sign up to set email alerts
|

We Need to Delay the Age of Onset of Alcohol Consumption

Abstract: In recent years, new consumption patterns, such as binge drinking, have increased among young people and have not always been recognized as problematic either by health personnel or by society in general, as they are intensive episodes, interspersed with no consumption periods. Although the prevalence of alcohol use disorders in the adult population continues to be higher in men than in women, these gender differences in relation to alcohol consumption are barely observed in adolescents between 14 and 18. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Onset of alcohol use was the strongest, following smokeless tobacco, and marijuana use the least. The current study aligns with previous ndings that the earlier onset of alcohol drinking, the more likely these individuals are to develop binge drinking and other alcohol use related problems [10,24]. However, some previous studies had contradicted ndings.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Onset of alcohol use was the strongest, following smokeless tobacco, and marijuana use the least. The current study aligns with previous ndings that the earlier onset of alcohol drinking, the more likely these individuals are to develop binge drinking and other alcohol use related problems [10,24]. However, some previous studies had contradicted ndings.…”
supporting
confidence: 90%
“…Another noteworthy limitation to the interpretation of our results is that the study failed to take age of rst intoxication by alcohol into consideration. While age of onset of alcohol use has been identi ed as an independent risk factor of binge drinking, previous studies [10,30] suggest that delay to intoxication may be an important determinant of negative alcohol use outcome and should be considered in the modelling. Although the NSDUH includes various substance use information, the study only includes the main three substances which are the most prevalent among binge drinking population.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticeable the delay in the age of onset of alcohol use from the age of 15 to 16 in 2016. Considering that an earlier age of onset has been found as a risk factor for RC and HED patterns [ 51 , 52 ], this delay should protect students against risky drinking behaviors. The effect of the age of alcohol onset was high in the three study periods, but the greatest effect was observed in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2019 National Survey on Drug Use and Health (NSDUH) data, almost 30% of adults ages 18 and older reported binge drinking in the past month 12 . The majority of previous studies, including some large-scale studies 13 , have established that early onset of drinking is a known risk factor for adulthood heavy drinking 14 16 . However, some inconsistent study findings suggested little to no evidence for this association, which might be contributed to different operational definitions of alcohol onset 15 , 17 .…”
Section: Introductionmentioning
confidence: 99%